MENINGKATKAN KUALITAS PENDIDIKAN DESA KARACAK LEUWILIANG MELALUI PEMBELAJARAN TAMBAHAN SEKOLAH ALAM JONG BOBAR (STUDI KASUS MI MATHLAUL ANWAR GELEDUG) - Mauludy Nugraha Nugraha (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2023)
This research purpose to provide efforts to improve the education quality of human resources especially students of MI Mathaul Anwar Geledug Karacak Leuwiliang. The urgency of this research is the inequality and limited access facilities to improve the quality of human resources so that additional learing is needed which is spearheaded by the youth community in Bogor Regency. The research method used is qualitative with field research observing how the activities and series of sekolah alam are carried out. Plus, I took advantage of sekolah alam Jong Bobar activities for observing. As for some of the activities Sekolah Alam such as including English classes, local history, literacy, and so on. Even though additional classes outside formal schools, there are obstacles to implementing such as limited funds, time, and low awareness of students and student guardians. However, on the other hand, there is a significant impact from the sekolah alam on the fourthgrade students of MI Mathlaul Anwar, namely intelligence, knowledge, and courage. This is caused by an effective teaching method in which we use joyful learning and gamification. Therefore, with this method we do devotion and build the village through improving the quality of education for MI Mathlaul Anwar students.